Economic valuation of two selected ecotourism sites in the Island Garden City of Samal - Timbol, Kimberly Jean H.
The study was designed to valuate two ecotourism sites in the Island garden City of Samal through the use of the travel cost method. Data were collected through survey questionnaires, interviews, and researches. Data collected- travel time, cost of travel, average daily income and number of visitors- were run and analyzed through regression analysis using SPSS. By tabulating the profiles of the visitors, it was found out that more males frequent the areas more often and that most respondents are students. The profile also showed that most respondents are from Samal. Results of the regression analysis show that the visitors value the areas at Php2048.4672.